Pengaruh Konseling KB Pada Ibu Hamil Trimester III terhadap Keikutsertaan KB Pasca Persalinan di Kecamatan Sukowono Kabupaten Jember (The Effects of Family Planning's Counseling Among Third Trimester Pregnancy Women to Participation of Postpartum Family P - Vita Khusnul Khotimah; Ni'mal Baroya; Pudjo Wahjudi (Pustaka Kesehatan, 2016)
Posttpartum family planning was very important to prevent unintended pregnancy. Based onthese data, Sukowono Subdistrict has lowest postpartum FP participant that was any 1 personthan another subdistrict. The low service caused by the lack of FP counseling treatmenttherefore it will impact to the increasing of unmet need. This research aims to know effects offamily planning's counseling among third trimester pregnancy women to participation ofpostpartum family planning in sukowono subdistrict, Jember District. This type of research wasquasi-experimental research with the type of Community Trial. The study was conducted inNovember 2014 until July 2015, in Sukowono Subdistrict. The total respondents were 45 peopleand the randomization ratio was 1:2 for the control and intervention groups. Result showed thatgroup that was given counseling have knowledge and attitude higher than group that was notgiven counseling The analysis results of FP counseling effect to postpartum FP participationshow experimental group percentage of respondents who participate to postpartum FP washigher than control group, and there was significant relationship between counseling treatmentand postpartum FP participation. The analysis results also showed there was no differencebetween planning and realization of postpartum FP participation in group that was given FPcounseling.Keywords: Family Planning's Counseling, Postpartum Family Planning